Jumping asymmetries and risk of injuries in preprofessional ballet - MacSweeney, N. D. H.; Shaw, J. W.; Simkin, G. P.; Pedlar, C. R.; Price, P. D.; Mahaffey, R.; Cohen, D. D. (The American Journal of Sports Medicine, 2024)
Background: Preprofessional ballet dancers are exposed to the risk of injuries, primarily in the lower extremities, with most injuries occurring during jumping and landing activities. Interlimb asymmetry during jumping and landing activities has been associated with the injury risk in adolescent athletes, but this has not been examined in dancers. Purpose: To investigate associations between interlimb asymmetry during a double-leg countermovement jump (DL-CMJ) and single-leg jump (SLJ) and the injury risk in adolescent preprofessional ballet dancers. Study Design: Cohort study; Level of evidence, 2. Methods: Adolescent preprofessional ballet dancers (N = 255) performed 3 DL-CMJs and 3 SLJs on force plates during annual screening. Absolute and directional (separate values for left and right limb dominance) asymmetries in a set of kinetic variables during a DL-CMJ and in jump height during an SLJ were calculated. Each variable was characterized as having "high" or "normal" asymmetry according to the percentage of asymmetry (greater than or less than or equal to, respectively, the mean ± 0.5 SD) based on the present sample. Risk ratios (RRs) and 95% CIs were calculated based on the injury incidence in the subsequent academic year. Results: Of the 242 dancers that satisfied the inclusion criteria, 128 injuries were observed in the subsequent academic year. In the whole sample, 3 absolute, 7 left limb-dominant, and 1 right limb-dominant kinetic asymmetry in the eccentric, concentric, and landing phases of the DL-CMJ as well as left limb-dominant jump height asymmetry in the SLJ were associated with a significant (P < .001) increase in the injury risk (RR, 1.28-1.69 [95% CI, 1.02-2.37]). Separating by sex, asymmetries in the eccentric and landing phase of the DL-CMJ were not significant in boys, while in girls, RRs for asymmetries in the eccentric and landing phase of the DL-CMJ increased, and SLJ jump height asymmetry was not significant. Conclusion: Higher asymmetries in certain kinetic variables during the DL-CMJ and in jump height during the SLJ were associated with an elevated risk of injuries in elite preprofessional ballet dancers with some sex-specific differences. Associations were mainly identified for high left limb-dominant asymmetry in the takeoff phase, suggesting that the injury risk may be specific to a relative right limb deficit.